2013
DOI: 10.1590/s1677-32252013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human enamel permeability exposed to bleaching agents

Abstract: Aim: To evaluate the human enamel permeability after different external bleaching techniques. Methods: The coronal portions of 20 maxillary human incisors were covered with an acid resistant varnish, except the labial surface, to prevent dye penetration of silver nitrate. The specimens were divided randomly into four groups (n=5) according to the bleaching treatments: Group 1 (G1)-without bleaching agent (control group), Group 2 (G2)-35% hydrogen peroxide (HP)-one session of three 10-min applications, Group 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(22 reference statements)
1
9
0
1
Order By: Relevance
“…The methodology of permeability analysis was based on previous studies 5,7,22 . After bleaching, all specimens, including the control group (n=32), were stored in a dark environment in artificial saliva for 48 h at 37 o C. The lingual and proximal surfaces and the CEJ were sealed with cyanoacrylate resin (Super Bonder Loctite, Henkel Ltda, São Paulo, SP, Brazil) and a nail varnish to prevent dye penetration of silver nitrate (tracer agent) through this area.…”
Section: Permeability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The methodology of permeability analysis was based on previous studies 5,7,22 . After bleaching, all specimens, including the control group (n=32), were stored in a dark environment in artificial saliva for 48 h at 37 o C. The lingual and proximal surfaces and the CEJ were sealed with cyanoacrylate resin (Super Bonder Loctite, Henkel Ltda, São Paulo, SP, Brazil) and a nail varnish to prevent dye penetration of silver nitrate (tracer agent) through this area.…”
Section: Permeability Analysismentioning
confidence: 99%
“…There is concern that bleaching agents (hydrogen peroxide and carbamide peroxide) bring some damage to enamel surface, like increased roughness [3][4] and permeability [5][6] . This effect was demonstrated in a previous study 7 where silver nitrate penetration in tooth structure after bleaching was performed and it was found that these agents might diffuse into dentin by opening channels in tooth structure.…”
Section: Introductionmentioning
confidence: 99%
“…The enamel is composed of inorganic material contains 97% of its total weight and essentially constituted of hydroxyapatite, 1% of organic material; primarily proteins such as amelogenin and enamelin, and 2% of water 15) . The organic layer is a semipermeable membrane that allows hydrogen peroxide to penetrate the tooth structure and react chemically with tooth discoloration and the tooth structure 16) . Enamel hardness is related to the mineral and protein content.…”
Section: Introductionmentioning
confidence: 99%
“…17 Perbedaan nilai rata-rata kekerasan mikro dentin dalam penelitian ini dapat juga dikarenakan berat molekul bahan bleaching yang rendah. 18 Hidrogen peroksida memiliki berat molekul lebih rendah (34,0147 g/mol) dibandingkan sodium perborat (153,86 g/mol). Berat molekul rendah dapat menyebabkan hidrogen peroksida berpenetrasi ke dalam struktur gigi dan melepaskan oksigen yang akan merusak ikatan ganda dari kandungan organik dan anorganik di dalam tubulus dentin.…”
Section: Pembahasanunclassified